Effects of acaricides used in coffee crops on the eggs and subsequent stages of green lacewing - Vilela, Michelle; Carvalho, Geraldo Andrade; Carvalho, César Freire; Vilas Boas, Matheus Alvarenga (Coffee Science - ISSN 1984-3909, 2010)
One of the most common predatory species in coffee agrosystems is Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae). Its maintenance, however, depends on the application of non-toxic pesticides. Thus, bioassays were carried out in laboratory conditions to evaluate the selectivity of the acaricides spirodiclofen (Envidor – 0.12 g a.i.L-1), fenpropathrin (Meothrin 300 – 0.15 and 0.30 g a.i.L-1), sulphur (Thiovit Sandoz – 4.0 and 8.0 g a.i.L-1 and, abamectin (Vertimec 18 CE – 0.0067 and 0.0225 g a.i.L-1) on this predator’s eggs. The C. externa eggs were directly sprayed using a Potter’s tower. The eggs were then placed in glass tubes and kept in a climatic chamber at 25±2oC, RH of 70±10% and 12 hour photophase. The pesticides were classified according to the recommendations of the IOBC. Fenpropathrin (0.30 g a.i.L-1) was harmful and fenpropathrin (0.15 g a.i.L-1) was moderately harmful to the green lacewing. The products spirodiclophen, sulphur and abamectin were moderately harmful to the predator. New assays in greenhouse and field conditions should be carried out to verify the toxicity of these compounds.